Nasal function before and after rapid maxillary expansion in children: A randomized, prospective, controlled study. (December 2018) - Ottaviano, G.; Maculan, P.; Borghetto, G.; Favero, V.; Galletti, B.; Savietto, E.; Scarpa, B.; Martini, A.; Stellini, E.; De Filippis, C.; Favero, L.
Abstract: Objectives: Children can well detect and respond to odours in order to have information about food and environment. Rapid Maxillary Expansion seems to improve dental and skeletal crossbite and increase nasal patency correcting oral respiration in children. A previous pilot study suggested that Rapid Maxillary Expansion may lead to improved N-Butanol olfactory thresholds, and peak nasal inspiratory flow values (PNIF). The aim of the present study was to prospectively evaluate olfactory threshold, nasal flows and nasal resistances in children aged from 6 to 11 years before and after Rapid Maxillary Expansion, comparing treated children with a control group of similar age, growth stage (prepubertal) and transversal skeletal deficiency. Methods: N-butanol olfactory thresholds, anterior active rhinomanometry (AAR) and PNIF were measured in 11 children (6–11 years) before (T0), immediately and 6 months after Rapid Maxillary Expansion application (T1 and T2 respectively), and in a control group of 11 children (6–11 years) whose members remained under observation for the period of the study. Results: Considering the study group, PNIF values improved at T1 respect to the T0 values (p = 0.003), while T2 values were significantly higher than T0 ones (p = 0.0002). N-Butanol Olfactory Threshold significantly improved at each control (p = 0.01, p = 0, 01 and p = 0.0003, for T1 vs T0, T2 vs T1, T2 vs T0 respectively). No differences on AAR values were found during the six months follow-up in this group. Considering the control group, no significant differences were found for any of the considered variables during the time of the study. Comparing the two groups, there was a significant increase of PNIF values in the study group compared to the control group (p = 0.003) at T1, which was even more evident six months after Rapid Maxillary Expansion (p = 0.0005). This improvement was not shown by AAR values. N-Butanol Olfactory Threshold showed a significant improvement at T2 respect to T1 (p = 0.002) and T0 (p = 0.0005). Conclusion: Rapid Maxillary Expansion seems to significantly improve the respiratory capacity of treated patients, at least in terms of PNIF, and their olfactory function, measured by N-Butanol Olfactory Threshold Test. Further studies should be performed to evaluate if also changes in nasal resistances, measured by AAR, could occur, maybe considering a larger group of subjects and possibly using 4-phase rhinomanometry in order to evaluate the effective resistances during the entire breath.